PENGARUH PENGGUNAAN MEDIA VIDEO TERHADAP HASIL PRATIKUM KIMIA PERTANIAN DI UNIVERSITAS MUARA BUNGO - Aswana, S.Pd., M.Pd (Pendidikan Matematika | STKIP YM Bangko, 2021)
This study aims to determine the effect of using video media on the results of agricultural chemistry practicum at Muara Bungo University (UMB) Academic year 2020/2021 This research is an experimental research. The population of this research is the study program of mining, civil, agrotechnology, animal husbandry and fishery resources with samples of the agrotechnology study program in the control class and the animal husbandry study program as the experimental class. The sampling technique used was random sampling. Data collection techniques using psychomotor questionnaires. The data analysis technique used is the independent t Test. The results showed that the average learning outcomes of the control class was 63.6 and the experimental class was 70.4, the t-count value was 2.715 > t table 2.052. This means that there is a significant difference between the learning outcomes of the experimental class using instructional video media and the control class that does not use video media, so that there is an effect of using video media on learning outcomes in agricultural chemistry practicum at Muara Bungo University for the 2020/2021 academic year.